The Essential of Introducing TOEFL at Twelfth Grade Students of SMK GKPI 1 Pematangsiantar - Juwita Nova Sinurat; Bonita Anjelina Sihombing; Setia Oktaviana Sirait; Aulia Agustina; Herman Herman; Junita Batubara (Abdimas Paspama, 2023)
The purpose of this study is to inform SMK GKPI 1 Pematangsiantar's class XII students about the TOEFL and its advantages. This research was conducted at SMK GKPI 1 Pematangsiantar involving 35 class XII TJTL students. This socializing action took place on January 10, 2024. It was delivered via lecture and question and answer format. This is a presentation of TOEFL content and its educational advantages. Three sessions were used to implement this socialization: a pre-test questionnaire about the TOEFL test, an explanation of the socialization material about the test, and a discussion session with a post-test to gauge the students' comprehension of the material. The socialization activity's outcomes demonstrate that the students who participated in the first socialization were unaware of and unaccustomed to the TOEFL. But as they were more socialized and learned more about the TOEFL, their comprehension grew and they became quite excited. When comparing the post-test results to the pre-test, it was evident that student scores had increased significantly by up to 30%. The findings indicated that the TOEFL is still not well understood by the students at SMK GKPI 1 Pematangsiantar. Nevertheless, following the socialist's explanation of the TOEFL introduction, the implementation team administered a post-test to gauge students' comprehension. According to the computational results, the post-test average was 62.8%. This unequivocally demonstrates that their comprehension improved following exposure to the TOEFL introduction